The Influence of Digital Literacy and Financial Literacy on the Performance of MSMEs: (An Empirical Study of MSMEs in Depok City) - Novi Yulianti Amilie; Udriyah Udriyah; Dwi Rachmawati (Neo Journal of economy and social humanities, 2026)
This study aims to analyze the effect of digital literacy and financial literacy on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Depok City by integrating the Resource-Based View (RBV) and Technology Acceptance Model (TAM) perspectives. This study departs from the phenomenon of quantitative growth of MSMEs that has not been fully followed by the strengthening of internal capabilities, particularly in the use of digital technology and business financial management. This study uses a quantitative approach with a survey method of 100 MSME actors selected through cluster sampling techniques in 11 sub-districts in Depok City. Data analysis was performed using multiple linear regression. The results show that digital literacy and financial literacy, both partially and simultaneously, have a positive and significant effect on MSME performance (p < 0.05). Financial literacy has a more dominant influence than digital literacy. The Adjusted R² value of 0.747 indicates that 74.7% of the variation in MSME performance can be explained by these two variables. These findings confirm that literacy-based intangible capabilities are strategic determinants of MSME performance in urban areas undergoing digital transformation. This study provides empirical contributions by strengthening the integrative model of digital and financial literacy as a source of MSME competitive advantage.